Hybrid Percutaneous Brachiofemoral Shunt and Open Abdominal Aortic Aneurysm Repair in a Kidney Transplant Recipient - Javad Salimi; Sayed Alimohammad Sadat; Mohammad Javad Yavari Barhaghtalab; Hormat Rahimzadeh (Case Reports in Vascular Medicine)
Abdominal aortic aneurysm (AAA) repair in kidney transplant recipients may cause ischemia in the transplanted kidney. As a result, various techniques have been described for protection of the renal allograft during AAA repair including temporary shunt, extracorporeal bypass, cold renal perfusion, endovascular aortic aneurysm repair (EVAR), and operation without renal allograft protection. We successfully treated a 56-year-old man, a case of kidney transplantation with AAA, using a temporary hybrid percutaneous brachiofemoral shunt using vascular prosthesis with a long 7-French (Fr) catheter sheath introducer (CSI) in the aortic arch via the right brachial artery and 8 Fr CSI in the right femoral artery that were connected together with a 7 Fr guiding catheter, before aortic cross-clamping and repair of AAA using a Dacron tube graft. The patient recovered well from the surgery without any complication and was discharged on the 6th postoperative day. To our knowledge, this is the first report of using a temporary hybrid percutaneous brachiofemoral shunt for renal allograft protection in AAA repair surgery in a patient with kidney transplantation, and we think that this temporary shunt is an easy, safe, and rapid method for renal allograft protection from ischemia.